2017
DOI: 10.1007/s11116-017-9774-2
|View full text |Cite
|
Sign up to set email alerts
|

Constrained nested logit model: formulation and estimation

Abstract: A model of traveller behaviour should recognise the exogenous and endogenous factors that limit the choice set of users. These factors impose constraints on the decision maker, which constraints may be considered implicitly, as soft constraints imposing thresholds on the perception of changes in attribute values, or explicitly as hard constraints. The purpose of this paper is twofold: (1) To present a constrained nested logit-type choice model to cope with hard constraints. This model is derived from the entro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For estimating passenger distributions in public transport applications the logit model is most commonly applied. To adjust to certain requirements, the logit model is constantly developed further, for example Espinosa-Aranda et al (2018) propose a constrained nested logit model to model passenger distributions on routes in public transport. Since recently, choice models in general and the logit model in specific are applied in optimization approaches for public transport applications.…”
Section: Passenger Route Choicementioning
confidence: 99%
“…For estimating passenger distributions in public transport applications the logit model is most commonly applied. To adjust to certain requirements, the logit model is constantly developed further, for example Espinosa-Aranda et al (2018) propose a constrained nested logit model to model passenger distributions on routes in public transport. Since recently, choice models in general and the logit model in specific are applied in optimization approaches for public transport applications.…”
Section: Passenger Route Choicementioning
confidence: 99%
“…The utilities for the passengers are calculated following the approach proposed in Espinosa-Aranda et al (2014). In this subsection we describe this approach and give an illustrative example.…”
Section: 1 Dynamic Utilities Modellingmentioning
confidence: 99%
“…In this computational experiment we have considered the utility functions based on Gaussian kernels estimated in Espinosa-Aranda et al (2014). The Table 9 Potential total trips ( g w ) Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Designed to relax the independence among all alternatives, the nested logit (NL) model proposed by McFadden (1978) identifies different substitution patterns and classifies similar products into the same nest. The studies of the NL model and its variants can be found in a lot of literature, such as transportation (Espinosa‐Aranda et al, 2018; Lu et al, 2017), facility location (Ramaul & Ramaul, 2018) and retailing (Chen & Jiang, 2020). Nevertheless, an inherent characteristic, an exponential preference function in terms of price, composes a strict constraint on the applicability of this model.…”
Section: Introductionmentioning
confidence: 99%